The relationship between dimensions of compensation satisfaction and employee performance among the employees of UBF Maintenance Sdn. Bhd / Nurdiyanah Md Yunus, Munira Mohd Ramadhan and Izura Ismail - Md Yunus, Nurdiyanah; Mohd Ramadhan, Munira; Ismail, Izura (2012)
This research is about a study on the relationship between dimensions of compensation satisfaction and employee performance that has chosen employees of UBF Maintenance Sdn. Bhd. as respondents. This research was to determine that there is an existence of correlation between these variables. This is a type of correlational research. The sampling frame is the employees of UBF Maintenance Sdn. Bhd. with population of 131 employees and by using stratified random sampling technique, 104 respondents were made as sample size. The unit of analysis is individual with the instrument of Likert Scale questions and close-ended questions. Questionnaire is used to collect the data and SPSS 17.0 data software analysis is used to compute the correlation of the variables. This research should make a contribution to the understanding of the relationship between dimensions of compensation satisfaction and employee performance for most private organizations in any industries, human resource practitioners and employees themselves. The result of the research shows that the variables are positively correlated with one other thus the hypotheses were accepted.